БОШЛАНҒИЧ ТАЪЛИМДА МАТННИ ТАҲЛИЛ ҚИЛИШ МЕТОДИ САМАРАДОРЛИГИНИ БАҲОЛАШ - Атаджанов, Х.Л.; Абдуразакова, Н.С. (SCIENCE and SOCIETY, 2025)
The article provides information on applying the text analysis method in reading literacy lessons and assessing the effectiveness of the text analysis method in primary education.
Keywords: education; assessment; reading literacy; method; pedagogical experience; text; experience; control